The Challenges of Implementation Greywater Recycling System In Residential Buildings - Soong, Hui Ni; Omar, Roshartini; Goh, Kai Chen; Seow , Ta Wee (Research in Management of Technology and Business, 2021)
The growth of sustainable construction has encouraged construction players to implement green technologies such as water efficiency technology into their projects. Even though Malaysia is not a country that lack of water resources, but water supply problems always been an issue due to water pollution, leakages and others reason. Malaysian’s daily freshwater consumption has over the standard set by WHO because they use potable water in gardening, and toilet flushing. This paper aims to identify the challenges and the readiness of Malaysian construction players in implementing greywater recycling systems in residential buildings as well as the strategies that should be used to increase the rate of implementation of this system. By achieving the objectives of this paper, a survey questionnaire been carried out among 91 out of 364 respondents with a 25% response rate in the construction industry such as developers, contractors, and construction authorities’ organization. This research found that the agreement of respondents towards challenges and strategies is high while their readiness to implement greywater recycling systems is moderate-high. Respondents agreed that lack of awareness and knowledge is the biggest challenge to implement greywater recycling systems, clients’ support readiness is low and construction industry authorities and government should implement strategies in education and certification to increase the implementation rate of these systems in Malaysia residential buildings. In conclusion, this research encourages construction players to understand the challenges and knowledge on greywater recycling systems and give more awareness to increase the implementation rate of these systems in future residential projects in Malaysia.